Analisis Akuntabilitas Dan Transparansi Dalam Praktik Tata Kelola Keuangan Berlandaskan Tri Hita Karana Di Pura Desa Lan Puseh Desa Adat Denpasar - Ni Komang Ayu Trisna; I Wayan Sudiana; I Made Endra Lesmana Putra (UNHI Press, 2026)
This study aims to analyze accountability and transparency in financial governance practices based on the Tri Hita Karana concept at Pura Desa lan Puseh Desa Adat Denpasar. The background of this research is driven by the importance of implementing good governance principles in managing funds of religious organizations, which are sourced from donations (punia), voluntary contributions, and other offerings. The research method used is descriptive qualitative, with data collection techniques including interviews, observations, and documentation. The informants consist of the traditional village head (Bendesa Adat), temple treasurer, priest (Pemangku), and temple administrators (Pengempon). Data analysis applies the Miles and Huberman model, and data validity is ensured through method triangulation. The results indicate that accountability practices have been implemented quite well, as reflected in regular financial recording, the use of transaction evidence, and the preparation of financial reports after activities. However, the recording system is still simple and not yet standardized. Meanwhile, transparency has not been optimal, as financial information is only shared in internal meetings and not publicly accessible to the wider community. From the Tri Hita Karana perspective, financial management reflects harmony in parahyangan, pawongan, and palemahan. However, improving transparency is necessary to strengthen public trust and achieve better financial governance.